ATI-2307 Exhibits Equivalent Antifungal Activity in Cryptococcus neoformans Clinical Isolates With High and Low Fluconazole IC50 - Gerlach, Elliot S.; Altamirano, Sophie; Yoder, J. Marina; Luggya, Tony S.; Akampurira, Andrew; Meya, David B.; Boulware, David R.; Rhein, Joshua; Nielsen, Kirsten (Frontiers in Cellular and Infection Microbiology, 2021)
Half maximal inhibitory concentrations (IC50) to the experimental drug ATI-2307 and complete inhibition (IC90) of the common clinically used antifungal drug amphotericin B were determined by microbroth dilution assay for a collection of 69 clinical isolates of Cryptococcus neoformans from Uganda that had high fluconazole IC50 values. The majority of the clinical isolates tested had fluconazole IC50 at or above 8 µg/mL, but were susceptible to both amphotericin B (IC90 ≤1 μg/mL) and ATI-2307 (IC50 ≤0.0312 µg/mL). No correlation between increased fluconazole minimum inhibitory concentration (MIC) and ATI-2307 or amphotericin B MIC was observed, suggesting that the cellular changes impacting fluconazole susceptibility did not impact the effectiveness of ATI-2307. Our results suggest that ATI-2307 is a promising new antifungal drug for use in the context of high fluconazole or other antifungal drug MICs and/or in combination drug therapy regimens.